Eurotium cristatum fermented okara as a potential food ingredient to combat diabetes - Chan, Li Yan (2020)
Type 2 diabetes mellitus (T2DM) is a chronic disease, and dietary modification is a crucial part of disease management. Okara is a sustainable source of fibre-rich food. Most of the valorization research on okara focused more on the physical attributes instead of the possible health attributes. The fermentation of okara using microbes originated from food source, such as tea, sake, sufu and yoghurt, were explored here. The aim of this study is to investigate fermented okara as a functional food ingredient to reduce blood glucose levels. Fermented and non-fermented okara extracts were analyzed using the metabolomic approach with UHPLC-QTof-MSE. Statistical analysis demonstrated that the anthraquinones, emodin and physcion, served as potential markers and differentiated Eurotium cristatum fermented okara (ECO) over other choices of microbes. The in-vitro α-glucosidase activity assays and in-vivo mice studies showed that ECO can reduce postprandial blood glucose levels. A 20% ECO loading crispy snack prototype revealed a good nutrition composition and could serve as a fundamental formulation for future antidiabetes recipe development, strengthening the hypothesis that ECO can be used as a novel food ingredient for diabetic management.